2019
DOI: 10.3390/ijms20205016
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Cleaved p18 Bax Levels Associated with the Kinetics of Neuronal Cell Death during Japanese Encephalitis Virus Infection

Abstract: Japanese encephalitis virus (JEV) infection induces uncontrolled neuronal apoptosis, leading to irreversible brain damage. However, the mechanism of JEV-induced neuronal apoptosis has not been clearly elucidated. This study aimed to investigate both virus replication and neuronal cell apoptosis during JEV infection in human neuroblastoma SH-SY5Y cells. As a result, the kinetic productions of new viral progeny were time- and dose-dependent. The stimulation of SH-SY5Y cell apoptosis was dependent on the multipli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Furthermore, the involvement of mitochondrion-dependent pathways in regulating JEV-induced neuronal apoptosis has also been elucidated. Infection of cultured neuronal cells caused the JEV NS2B-NS3 protease-induced or p21-Bax/p18-Bax-mediated release of mitochondrial cytochrome C in the cytoplasm, indispensable for the activation of caspase-3/7-mediated apoptosis pathways in these cells [ 54 , 55 ]. Alternatively, the production of ROS and the stimulation of ASK1/ERK1/p38-MAPK pathway in infected cells is also linked to the NS4B-NS3-induced mitochondrion-dependent apoptosis [ 54 , 56 ].…”
Section: Apoptosismentioning
confidence: 99%
“…Furthermore, the involvement of mitochondrion-dependent pathways in regulating JEV-induced neuronal apoptosis has also been elucidated. Infection of cultured neuronal cells caused the JEV NS2B-NS3 protease-induced or p21-Bax/p18-Bax-mediated release of mitochondrial cytochrome C in the cytoplasm, indispensable for the activation of caspase-3/7-mediated apoptosis pathways in these cells [ 54 , 55 ]. Alternatively, the production of ROS and the stimulation of ASK1/ERK1/p38-MAPK pathway in infected cells is also linked to the NS4B-NS3-induced mitochondrion-dependent apoptosis [ 54 , 56 ].…”
Section: Apoptosismentioning
confidence: 99%
“…A previous study demonstrated that JEV induced apoptosis in SH-SY5Y cells via the activation of the caspase-3/7 pathway in a time-dependent manner. 26 Similarly, we found that DTMUV KPS54A61 and JEV JaGAr-01 could induce apoptosis in DN and CCL-141 probably via the caspase-3dependent pathways (Figures 3b-e, 4, 5). However, higher numbers of DN and CCL-141 cells infected with DTMUV KPS54A61 underwent apoptosis compared with cells infected with JEV JaGAr-01 (Figure 3d,e).…”
Section: Discussionmentioning
confidence: 51%
“…[21][22][23][24] It is known that JEV infects various mammalian neuronal cell types and causes neuronal death. [25][26][27] However, the pathogenesis of JEV infection in birds including viral neurotropism and innate immune response has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The flaviviruses infection is capable of triggering multiple apoptotic pathways, such as mitochondria-dependence ( Suzuki et al., 2018 ), death receptor ( Liao et al., 2010 ), and endoplasmic reticulum ( ER ) stress ( Huang et al., 2016 ; Turpin et al., 2021 ). JEV triggered apoptosis of N18 (a mouse neuroblastoma cell line) cells through the mitochondrial pathway ( Tsao et al., 2008 ), possibly by inducing proteolysis of endogenous p21 BAX to produce p18 BAX in SH-SY5Y cells (human neuroblastoma) ( Wongchitrat et al., 2019 ). ZIKV induced neuronal apoptosis by increasing mitochondrial fragments ( Yang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%